ANALISIS PENERAPAN SISTEM TRANSAKSI NON TUNAI (TNT) PADA DINAS LINGKUNGAN HIDUP KOTA PARIAMAN - Elsa Fitri Amran; Basrefnaldi Basrefnaldi; Silfira Silfira (IAIN BATUSANGKAR, 2021)
This research is a descriptive analysis of qualitative research against the application of Transaction analysis non cash (TNT) at the environmental agency of Pariaman. The purpose of this research is to know how the application of the System transactions are Non cash and knowing the constraints faced in the implementation of Non cash transaction system at the service of the Environment Pariaman. In this study using data collection techniques by means of observation, documentation, and interviews are then analyzed and interpreted from the data obtained by using a descriptive analysis method. The results of this research to show that the execution of the transaction system Non cash At the environmental agency of Pariaman has sought to carry out the transaction of non cash in accordance with the applicable rules and the constraints faced in the implementation of the Non cash transaction system in the Pariaman City Environmental Agency is about a lack of socialization about the use of the Nagari Cash Management Application, the internet network that are not yet adequate, and there are still those who are less advance in respect of the operation technology also the system is still not perfect.